2000
DOI: 10.7164/antibiotics.53.105
|View full text |Cite
|
Sign up to set email alerts
|

TMC-95A, B, C, and D, Novel Proteasome Inhibitors Produced by Apiospora montagnei Sacc. TC 1093. Taxonomy, Production, Isolation, and Biological Activities.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
137
0
8

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(147 citation statements)
references
References 16 publications
2
137
0
8
Order By: Relevance
“…Generally, α,β-unsaturated ketones with electron-donating groups gave higher yields than those with electron-withdrawing groups (Table 2, entries 2, 10 vs. [3][4][5][6][7][8]. Ortho-and meta-substituted α,β-unsaturated ketones gave higher yields than para-substituted α,β-unsaturated ketones ( Table 2, entries 2-5 vs. [8][9][10][11]. α,β-Unsaturated ketones bearing naphthyl and heterocyclic substituents participated in smooth aldol reactions in 81% and 88% yield, respectively (Table 2, entries 13,14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, α,β-unsaturated ketones with electron-donating groups gave higher yields than those with electron-withdrawing groups (Table 2, entries 2, 10 vs. [3][4][5][6][7][8]. Ortho-and meta-substituted α,β-unsaturated ketones gave higher yields than para-substituted α,β-unsaturated ketones ( Table 2, entries 2-5 vs. [8][9][10][11]. α,β-Unsaturated ketones bearing naphthyl and heterocyclic substituents participated in smooth aldol reactions in 81% and 88% yield, respectively (Table 2, entries 13,14).…”
Section: Resultsmentioning
confidence: 99%
“…This kind of compounds have become important synthetic targets as these structural frameworks form the core units of many natural products and pharmaceutically active compounds [1]. Convolutamydines [2], arundaphine [3], donaxaridine [4], dioxibrassinine [5], maremycins [6], paratunamide [7], celogentin K [8], TMC-95A-D [9], flustraminol [10], 3-hydroxy welwitindolinones [11] and CPC-1 [12] are some examples of a growing list of bioactive 3-substituted-3-hydroxy-2-oxindole natural products (Figure 1). …”
Section: Introductionmentioning
confidence: 99%
“…Selective inhibitors of the proteasome show great promise as novel anticancer agents since tumor cells are more sensitive than normal cells to proteasome-inhibition-induced apoptosis. [26][27][28] TMC-95A (1) and its diastereoisomers TMC-95B -D(2 -4), recently isolated as fermentation products of Apiospora montagnei, [29] represent a new class of selective proteasome inhibitors (Scheme 1). These molecules are structurally characterized as novel cyclic peptides containing L-tyrosine, L-asparagine, highly oxidized L-tryptophan, (Z)-1-propenylamine (Z=benzyloxycarbonyl), and 3-methyl-2-oxopentanoic acid moieties.…”
Section: Introductionmentioning
confidence: 99%
“…These molecules are structurally characterized as novel cyclic peptides containing L-tyrosine, L-asparagine, highly oxidized L-tryptophan, (Z)-1-propenylamine (Z=benzyloxycarbonyl), and 3-methyl-2-oxopentanoic acid moieties. [30] Biological studies [29] showed that TMC-95A inhibited the CT-L, TL, and PGPH activities of 20S proteasome with IC 50 values (IC 50 =concentration required for 50% inhibition) of 5.4, 200, and 60nM, respectively. TMC-95B inhibited these activities to the same extent as TMC-95A, while TMC-95C and D were 20 -150 times weaker inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…In early 2000, Kohno and coworkers (5) reported the isolation of novel cyclic tripeptides TMC-95A-D (1-4) (Fig. 1).…”
mentioning
confidence: 99%